A comparative study of the results of endoscopic dacryocystorhinostomy with and without stent placement - Shah, Shaili S.; Ganvit, Shruti G.; Ambani, Kirti P.; Katarkar, Ashish U. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Aim and objectives were to evaluate and compare the outcomes of endoscopic dacryocystorhinostomy (DCR) with and without silicone stenting. Surgical success was assessed both subjectively and objectively. Methods: A retrospective study was conducted. Total 30 patients with acquired NLD obstruction were enrolled in the study. The patients who underwent the surgery were randomly assigned into two groups: group I: with silicone stent placement, group II: without stent placement. The patients were evaluated in terms of symptoms relief (subjective assessment) and patency of neo-ostium (objective assessment). Results: In our study, success rate for patients with placement of stent was 91.66% and without stenting was 77.77%. Statistical data proved that, there was no significant difference between two groups. Endoscopic DCR with stenting had good long term outcome. It maintains patency and prevents re-closer of neo-ostium. With stenting cases cause of failure was synechiae formation and in without stenting cases causes was infection, granulation formation and stoma closer. So both cases had their own merits and demerits. Conclusions: The endoscopic DCR is minimally invasive and simple procedure. Patient’s discomfort, synechiae, granulations are drawbacks of stenting but stents had given good long term outcome in maintaining patency of neo-ostium. Still data proved, there was no significant difference in both groups. This was due to our small sample size. Regular follow up is necessary for better post-operative outcome and prevention of further complications. So ultimately it is surgeon choice and level of expertise decides use of stent in DCR.